2013
DOI: 10.20452/pamw.1776
|View full text |Cite
|
Sign up to set email alerts
|

Emerging concepts and therapies for chronic obstructive pulmonary disease

Abstract: REVIEW ARTICLE Emerging concepts and therapies for chronic obstructive pulmonary disease 303 Diagnosis and symptom identification The cornerstone for the diagnosis of chronic obstructive pulmonary disease (COPD) remains evidence of airflow obstruction on spirometry with the forced expiratory volume in 1 second (FEV 1 ) to forced vital capacity ratio of less than 70%.1 Patients with compatible symptoms require spirometry to confirm airway obstruction, and FEV 1 is still used as the marker of the grade of COPD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…14 De Mi chelis et al and Raghavan et al in their study showed a significant reduction in ICU admissions, length of hospital stay, increase in survival rates, and decrease in the number of tracheostomies related to COPD exacerbations. 15,16 Therefore, NIV is effective in management of acute exacerbation of chronic obstructive pulmonary disease along with antibiotics and bronchodilators.…”
Section: Observation and Resultsmentioning
confidence: 99%
“…14 De Mi chelis et al and Raghavan et al in their study showed a significant reduction in ICU admissions, length of hospital stay, increase in survival rates, and decrease in the number of tracheostomies related to COPD exacerbations. 15,16 Therefore, NIV is effective in management of acute exacerbation of chronic obstructive pulmonary disease along with antibiotics and bronchodilators.…”
Section: Observation and Resultsmentioning
confidence: 99%